Analisis Subtitusi Input Pupuk pada Produksi Tanaman Kubis di kelurahan Rurukan Kecamatan Tomohon Timur Kota Tomohon. - Besanof S. Mandagi; Jen Tatuh; Gene H.M. Kapantow; Loraine W. Th. Sondak (COCOS, 2013)
ABSTRACTThe objective of this research is to determine the possibility of inputsubstitution organic fertilizer and inorganic fertilizer by measuring MRTS(marginal rate of technical subtitution) Cabbage crop production in RurkanVillage East Tomohon Subdistrict. The method used in this study is surveymethod. This study uses primary data and secondary data, which primary dataobtained through in-depth interviews with 6 cabbage farmers who have switchedto organic fertilizer and 14 farmers who are still in the process of transition to useorganic fertilizers, so the total number of samples in this study is 20 cabbagefarmers, while the secondary is obtained from the Rurukan Village Office.Sampling method used in this research is purposive sampling.Data analysis methods used in this research is by using the model ofexponential cobb-douglas and proceed with the analysis of MRTS (Marginal Rateof Technical Subtitution) to measure the reduction of the quantity of one input byone additional unit of input quantity, in such a way that still produces the sameoutput level. The results are presented descriptively by using tables and verbaldescriptions.The result of research showed that of the five input variables taken turns at Î±= 5%, only organic fertilizer and inorganic fertilizers that had a significant effectin cabbage production. While the addition of land, seed, pesticides and labor hadno significant effect for the addition of cabbage production. The MRTS value was1,96 means that it is reguired 1,96 unit of organic fertilizers to substitute 1 unit ofinorganic fertilizers.2